Computational Methods for Risk Management in Economics and Finance - Resta, Marina (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
At present, computational methods have received considerable attention in economics and finance as an alternative to conventional analytical and numerical paradigms. This Special Issue brings together both theoretical and application-oriented contributions, with a focus on the use of computational techniques in finance and economics. Examined topics span on issues at the center of the literature debate, with an eye not only on technical and theoretical aspects but also very practical cases.